Factors Influencing Publication Rates among Counselor Educators - Sean Newhart; Patrick R Mullen; Ashley J Blount; W. Bryce Hagedorn (Teaching and Supervision in Counseling, 2020)
Factors influencing publication rates were examined among a simple random sample of 257 counselor educators. The factors of: a) gender, b) experience as a counselor educator, c) faculty rank, and d) working in a research institution predicted peer-reviewed publication rates in the counselor educator sample, with a large effect size. Additional results, limitations of the investigation, areas for future research, and implications for counselor educators are discussed.
Keywords: counselor educators; publication rates; faculty